Mitochondrion-Localized SND1 Promotes Mitophagy and Liver Cancer Progression Through PGAM5 - Liang, Shiwei; Zhu, Chuxu; Suo, Caixia; Wei, Haoran; Yu, Yingxuan; Gu, Xuemei; Chen, Liang; Yuan, Mengqiu; Shen, Shengqi; Li, Shiting; Sun, Linchong; Gao, Ping (Frontiers in Oncology, 2022)
Staphylococcal nuclease domain-containing protein 1 (SND1) is an evolutionarily conserved multifunctional protein that functions mainly in the nucleus and cytoplasm. However, whether SND1 regulates cellular activity through mitochondrial-related functions remains unclear. Herein, we demonstrate that SND1 is localized to mitochondria to promote phosphoglycerate mutase 5 (PGAM5)-mediated mitophagy. We find that SND1 is present in mitochondria based on mass spectrometry data and verified this phenomenon in different liver cancer cell types by performing organelle subcellular isolation. Specifically, The N-terminal amino acids 1-63 of SND1 serve as a mitochondrial targeting sequence (MTS), and the translocase of outer membrane 70 (TOM 70) promotes the import of SND1 into mitochondria. By immunoprecipitation-mass spectrometry (IP-MS), we find that SND1 interacts with PGAM5 in mitochondria and is crucial for the binding of PGAM5 to dynamin-related protein 1 (DRP1). Importantly, we demonstrate that PGAM5 and SND1-MTS are required for SND1-mediated mitophagy under FCCP and glucose deprivation treatment as well as for SND1-mediated cell proliferation and tumor growth both in vitro and in vivo. Aberrant expression of SND1 and PGAM5 predicts poor outcomes in hepatocellular carcinoma (HCC) patients. Taken together, these findings establish a previously unappreciated role of SND1 and the association of mitochondrion-localized SND1 with PGAM5 in mitophagy and tumor progression.